2014
DOI: 10.3233/xst-140427
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physician practice on patient radiation dose during CT guided biopsy procedures

Abstract: PURPOSE: Patient radiation dose during Computed Tomography (CT) guided biopsy procedures is determined by both acquisition technical parameters and physician practice. The potential effect of the physician practice is of concern. This study is to investigate the effects of those intangibles on patient radiation dose. METHODS: Patient radiation dose from 252 patients who underwent CT guided biopsy from 2009 to 2010 were retrospectively studied. Ten physicians who used conventional intermittent shots, low mA dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…The DLP values obtained in this study were observed to surpass the 3rd quartile values proposed by Weir et al specifically for the purpose of tumor ablation in thoracic or abdominopelvic regions [18]. It is important to note, however, that Weir's study was conducted within the confines of a single medical center for each CT scan, and the DRLs they put forward primarily reflected localized practices, lacking the consideration of the substantial variabilities that have been previously highlighted.…”
Section: Discussioncontrasting
confidence: 55%
“…The DLP values obtained in this study were observed to surpass the 3rd quartile values proposed by Weir et al specifically for the purpose of tumor ablation in thoracic or abdominopelvic regions [18]. It is important to note, however, that Weir's study was conducted within the confines of a single medical center for each CT scan, and the DRLs they put forward primarily reflected localized practices, lacking the consideration of the substantial variabilities that have been previously highlighted.…”
Section: Discussioncontrasting
confidence: 55%
“…The magnitude of the time influence, and how that combines with BMI to give the inverse gamma error requires further study. We did not have enough data on the physicians involved in all cases to perform a useful analysis, but a previous study [22] showed that, while physician practice played a role in CT guided biopsies, experience was less a factor. In plotting the BMI distributions in figure 5, we chose to present the data for combined BMI for doses below and above 100 mGy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the need for a smaller number of intra-procedural scans shortens the procedural times and improves comfort for the patient, who is required to maintain the same position for the entire duration of the procedure so that a mismatch between the CT acquisition volume and the real patient's position is not generated. On the contrary, standard CT-guided methods usually provide a higher number of CT scans to check the correct positioning and direction of the instrument, even after small advances or repositioning, weighing on the total radiation dose and on procedural times [34]. Moreover, SIRIO permits avoidance of damage to vulnerable structures near the lesions, such neuro-vascular bundles, allowing a prompt repositioning of the instrument.…”
Section: Discussionmentioning
confidence: 99%